Longitudinal study of factors associated with the anti-cancer efficacy and liver function in HCC patients treated with TACE in combination with percutaneous ablation - Ren, Huhu; Chen, Jian; Wu, Zhiqun; Li, Chen (Frontiers in Oncology, 2025)
BackgroundHepatocellular carcinoma (HCC) is a major cancer challenge worldwide. Combination therapy using transcatheter arterial chemoembolization (TACE) and percutaneous ablation offers potential for improved outcomes.ObjectiveTo evaluate the efficacy and liver function preservation in HCC patients treated with combined TACE and percutaneous ablation, identifying key prognostic factors.MethodsThis longitudinal study included 200 HCC patients. Factors analyzed included tumor characteristics, liver function tests, and serologic markers. Statistical analyses determined associations with treatment outcomes and survival.ResultsSmaller tumors (≤5.0 cm) and lower AFP levels (<200 ng/mL) were associated with higher treatment efficacy, with an objective response rate of 67.3% for lower AFP levels versus 42.3% for higher levels. Liver function was better preserved in patients with lower AFP levels (78.2% vs. 57.7%). Tumor size and liver stiffness significantly influenced survival and liver function outcomes.ConclusionThe combination of TACE and percutaneous ablation enhances outcomes in HCC, guided by specific prognostic markers. This supports the need for personalized approaches in HCC treatment and further research into combination therapies.